Pengaruh Self Control, Financial Technology dan Lingkungan Sosial terhadap Perencanaan Keuangan Mahasiswa Universitas Muhammadiyah Ponorogo - Suryani, Dinda Maulina; Rapini, Titi; Wahyuningsih, Dwi Warni (JURNAL ILMIAH EDUNOMIKA, 2025)
AbstractThis study was conducted to evaluate the impact of the influence of self-control, financial technology, and social environment on the financial planning of Muhammadiyah Ponorogo University students. This study is a quantitative type of research, with the method of data collection through a Likert scale-based questionnaire. A total of 190 respondents, proportionally selected from various faculties, became the sample source of this study. The data from the research results were processed using SPSS 25. By going through the normality test, classical assumption test, multiple linear regression test, determination test and hypothesis testing. The results showed that self control partially and simultaneously affects financial planning. Because self control has a significant influence in controlling consumptive behavior and encouraging better financial management. Financial technology partially and simultaneously affects financial planning, although it provides convenience in financial transactions financial technology can trigger excessive spending if not used wisely. The social environment also partially and simultaneously affects financial planning in shaping student spending patterns, where interactions with peers often influence financial decisions, both positively and negatively.Keywords: Self Control, Financial Technology, Social Environment, Financial Planning